Pengusaha Kecil Naik Kelas, Pelatihan Wirausaha Desa Tingkat Provinsi Jawa Barat - Sukandi, Pipin (Jurnal Abdimas Multidisiplin, 2023)
Purpose: Sociologist David McClelland said that, if you want a developed country, at least 2% of the population is an entrepreneur. This was realized by the West Java provincial government to continue to intensify entrepreneurship training for the community, especially in Bandung Regency. Method: This method was carried out offline in the form of entrepreneurial training for the community in Bandung Regency, starting with developing an entrepreneur’s mindset to create jobs for themselves and the surrounding community. Results: The results will be continuous training,  and in the future, it is hoped that there will be mentoring for those who open entrepreneurs. Limitation: The limitation of this activity is in terms of time and cost, so it can only be implemented for the people of Bandung Regency, West Java Province.